Green investment is a development alternative outside the hydrocarbon sector in Algeria - presentation of the solar energy projectt SSB in Algeria. - Abderahmani CHOUAIB, (Journal of North African Economies, 2025)
Algeria's increasing interest in renewable energies is embodied in undertaking a number of measures in light of reliance on a strategic national program that extends to the horizon of 2030, which includes pioneering projects, especially in the field of solar energy and wind energy, and supporting it with regulatory and legal methods that encourage the development of renewable energy because of its great importance in achieving Sustainable development, which is what was highlighted through this paper by highlighting the most important projects in this field, where the role assigned to energies is mainly to meet the demand for energy in isolated places and far from renewable electricity and gas networks within the framework of the national energy policy at the present time in the natural Which makes the efforts made in this field far from hoped for. Algeria's move towards a green economy is a strategic energy choice that contributes to preparing the country for the transition to a new and sustainable economy for current and future generations, similar to renewable energies that support the transition towards a sustainable formula for the Algerian economy.